Molecular cloning and preliminary functional analysis of six RING-between-ring (RBR) genes in grass carp (Ctenopharyngodon idellus). Issue 87 (April 2019) - Luo, Lifei; Zhu, Denghui; Huang, Rong; Xiong, Lv; Mehjabin, Rumana; He, Libo; Liao, Lanjie; Li, Yongming; Zhu, Zuoyan; Wang, Yaping
Abstract: Ubiquitination is a post-translational modification of proteins that is widely present in eukaryotic cells. There is increasing evidence that ubiquitinated proteins play crucial roles in the immune response process. In mammals, RING-between-RING (RBR) proteins play a key role in regulating immune signaling as the important E3 ubiquitin ligases during ubiquitination. However, the function of RBR in fish is still unclear. In the present study, six RBR genes ( RNF19A, RNF19B, RNF1 44AA, RNF1 44AB, RNF144B and RNF217 ) of grass carp ( Ctenopharyngodon idellus ) were cloned and characterized. Similar to mammals, all six members of RBR family contained RING, in-between-ring (IBR) and transmembrane (TM) domains. These genes were constitutively expressed in all studied tissues, but the relative expression level differed. Following grass carp reovirus(GCRV) infection, the expression of six RBR genes in liver, gill, spleen and intestine significantly altered. Additionally, their expression in Ctenopharyngodon idellus kidney (CIK) cells was significantly increased after GCRV infection. And deficiency of RNF144B in CIK with small interference RNA (siRNA) up-regulated polyinosinic:polycytidylic acid poly(I:C))-induced inflammatory cytokines production, including IFN-I, TNF-α, IL-6, and transcription factor IRF3, which demonstrated that RNF144B was a negative regulator of inflammatory cytokines. Our results suggested that the RBR might play a vital role in regulating immune signaling and laid the foundation for the further mechanism research of RBR in fishes. Highlights: Six RING-between-RING ( RBR ) genes from Ctenopharyngodon idellus were cloned for the first time. RNF144AA, RNF144AB, and RNF144B responded substantially after GCRV challenge. Poly (I: C)-induced proinflammatory cytokines were up-regulated by RNF144B silencing. The expression of RNF144B in liver, especially in intestine was intensely up-regulated at 1 day post–infection.